FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN HUTANG PERUSAHAAN NON KEUANGAN YANG TERDAFTAR DALAM BURSA EFEK INDONESIA - DENNYS SURYA; DEASY ARIYANTI RAHAYUNINGSIH (Jurnal Bisnis dan Akuntansi, 2012)
The main objective of this research is to test and analyze the effect of insider ownership, institutional ownership, dividen policy, asset structure, profitability, firm growth, business risk, size and investment opportunity set on debt policy. Sample in this research consists of 46 non financial companies which listed in the Indonesia Stock Exchange (Bursa Efek Indonesia) from 2009 until 2011. This research uses multiple linear regression to test the hypothesis. Result of this research shows that asset structure, profitability,size and investment opportunity set have an effect towards debt policy. In the other hand, insider ownership, institutional ownership, dividen policy, firm growth and business risk do not have an effect towards debt policy.